A helix-based cobalt(II) coordination polymer with mixed ligands of homophthalic acid and 2, 5-Bis(4′-pyridyl)-1, 3, 4-oxadiazole: synthesis, structure and magnetic property. Issue 7 (3rd July 2022) - Ju, Feng-Yang; Li, Yun-Ping; Liu, Guang-Zhen
Abstract: A novel Cobalt(II) coordination polymer formulated as [Co(hmph)(4-bpo)(H2 O)]n (1 ) was obtained through hydrothermal method, and then characterized by single-crystal X-ray diffraction, elemental analysis and powder X-ray diffraction (H2 hmph = homophthalic acid, 4-bpo = 2, 5-bis(4′-pyridyl)-1, 3, 4-oxadiazole). Complex 1 displays a three-dimensional architecture based on interweaving helix chains, which can be defined as a 4-connected uoc network with the Schläfli symbol of (4 2 .8 4 ). TGA experiment reveals that complex 1 can maintain its integrity until 214 °C. Furthermore, the magnetic data indicate there is weak antiferromagnetic interaction between the neighbor Co(II) atoms in the metal-carboxylate chain.